Análisis dotacional según estudios de casos sobre ciudades declaradas como Universitarias en España, México y Ecuador - Palate Pimbo, Fernanda Maricela (2020)
The university cities in Spain (Alcalá de Henares), Mexico (Puebla de Zaragoza), and Ecuador (Santa Ana de los Cuatro Ríos de Cuenca), are undergoing very rapid changes. These issues affect their environmental bases like mobility, equipment, population, buildability, and higher education in the increasingly open urban system. Thus, an endowment analysis is carried out based on a case study, which allows knowing the primary urban endowments that a city declared as a university has. For data collection, a multivariate matrix was used, which is divided into three levels, from the most general (five areas and eight categories) to the most specific (24 variables). Results showed that the city Alcalá de Henares is at an improved level, Puebla de Zaragoza is at a satisfactory level, and the city of Cuenca is at an insufficient level. It was then clear that in Alcalá de Henares and Puebla de Zaragoza being university cities planned since their inception, they provide better living conditions because their urban development has been projected and controlled over time. However, in the city of Cuenca, the same characteristics are identified but with deficiencies since this city was not planned from the beginning with this university city model but in an effort to adapt with constant demonstrating a firm change in its urban projection